Differential molecular biomarker expression in corals over a gradient of water quality stressors in Maunalua Bay, Hawaii - Tisthammer, Kaho H.; Martinez, Jonathan A.; Downs, Craig A.; Richmond, Robert H. (Frontiers in Physiology, 2024)
Coral reefs globally face unprecedented challenges from anthropogenic stressors, necessitating innovative approaches for effective assessment and management. Molecular biomarkers, particularly those related to protein expressions, provide a promising avenue for diagnosing coral health at the cellular level. This study employed enzyme-linked immunosorbent assays to evaluate stress responses in the coral Porites lobata along an environmental gradient in Maunalua Bay, Hawaii. The results revealed distinct protein expression patterns correlating with anthropogenic stressor levels across the bay. Some proteins, such as ubiquitin and Hsp70, emerged as sensitive biomarkers, displaying a linear decrease in response along the environmental gradient, emphasizing their potential as indicators of stress. Our findings highlighted the feasibility of using protein biomarkers for real-time assessment of coral health and the identification of stressors. The identified biomarkers can aid in establishing stress thresholds and evaluating the efficacy of management interventions. Additionally, we assessed sediment and water quality from the inshore areas in the bay and identified organic contaminants, including polycyclic aromatic hydrocarbons and pesticides, in bay sediments and waters.